The concept of Kazakh repatriation: characteristics, type and specifics - Bulbul, Shaken (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The article examines the dynamics and causes of changes in the scientific research over thirty years of such terms as "Kazakhs from abroad", "oralman", "kandas", "repatriates", which are the concept of Kazakh repatriation and its equivalent. The relevance of repatriation and related problems as well as consequences arising in Kazakhstan's conditions is not based on formulas accepted in the world, but using individual (in historical, regional, and ethnic contexts) special theories and methods. Taking into account the legal and social reasons that have contributed to the change of the concept of ethnic migration over the past 30 years, it can be concluded that the scientific terms arising from the legal status and public opinion are invalid. In addition, the article provides comparisons of the international experience of repatriation on the example of Israel, Turkey, Germany, Russia, Poland, Korea, Japan, etc. and discusses terms that can fully characterize the migration processes of ethnic Kazakhs. The objective formulation of the problem and definition of ethnic migration in Russian science creates conditions for the appearance of research terms in this area.